Atmospheric-pressure synthesis of glycerol carbonate from CO2 and glycerol catalyzed by protic ionic liquids. Issue 21 (16th August 2022) - Luo, Cong; Wang, Jiayi; Lu, Houfang; Wu, Kejing; Liu, Yingying; Zhu, Yingming; Wang, Binshen; Liang, Bin
Abstract : Under atmospheric pressure, a synthesis of glycerol carbonate was achieved in the one-pot reaction of CO2, glycerol, and styrene oxide with a 94% yield. Abstract : An ideal strategy for the management of greenhouse gas carbon dioxide (CO2 ) and surplus industrial product-glycerol (Gly) is to convert them into the valuable glycerol carbonate (GC). However, conventional conversion processes rely on high CO2 pressure and reaction temperature. In this work, a series of easily prepared protic ionic liquids (ILs) were studied for the one-pot synthesis of GC using CO2, Gly, and styrene oxide (SO). A 94% yield of GC was obtained with the catalysis of 1, 8-diazabicyclo[5.4.0]undec-7-enenium iodide (HDBUI) under atmospheric pressure at 45 °C. Experimental results and density functional theory (DFT) calculations suggest that the high catalytic activity of HDBUI is attributed to the strong nucleophilicity and substrate activation afforded by the synergistic effect of the protic HDBU + cation and I − anion. In addition, high GC yields were also obtained when simulated flue gas and crude Gly were used as substrates.